1997
DOI: 10.1099/00221287-143-6-2039
|View full text |Cite
|
Sign up to set email alerts
|

The genetic structure of Escherichia coli populations in feral house mice

Abstract: Escherichia coli was isolated from feral house mice (Mus domesticus) during the course of a mouse plague in the state of Victoria, Australia. Two farms were sampled over a period of 7 months and a total of 447 isolates were collected. The isolates were characterized using the techniques of randomly amplified polymorphic DNA and multi-locus enzyme electrophoresis. The mean genetic diversity of this E. coli population (H = 024) was found to be substantially lower than the diversity of an E. coli population repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 29 publications
8
51
1
Order By: Relevance
“…Whittam et al (1983) reported that about 2 % of the allelic diversity in E. coli isolated from humans living on three continents was explained by a geographical effect. In a study of E. coli isolated from two populations of feral house mice, Genetic structure of enteric bacteria 15 km apart, locality was found to explain about 5 % of the genetic variation (Gordon, 1997). These values are comparable to those observed in this study for E. coli (4-6 %).…”
Section: Population Structuresupporting
confidence: 76%
See 1 more Smart Citation
“…Whittam et al (1983) reported that about 2 % of the allelic diversity in E. coli isolated from humans living on three continents was explained by a geographical effect. In a study of E. coli isolated from two populations of feral house mice, Genetic structure of enteric bacteria 15 km apart, locality was found to explain about 5 % of the genetic variation (Gordon, 1997). These values are comparable to those observed in this study for E. coli (4-6 %).…”
Section: Population Structuresupporting
confidence: 76%
“…Although studies of electrophoretic variation at multiple enzyme loci (MLEE) has provided much support for the clonal paradigm, especially for Escherichia coli (Milkman, 1973 ;Selander & Levin, 1980 ;Caugant et al, 1981Caugant et al, , 1984Whittam et al, 1983 ;Pupo & Richardson, 1995 ;Gordon, 1997), the results of these studies have also highlighted some of the problems with the concept. Maynard Smith (1991) maintains that two observations are common in the majority of MLEE studies : (1) bacterial populations exhibit extensive genetic diversity ; and (2) populations are ' clonal ', that is, the same haplotype is recovered repeatedly.…”
Section: Introductionmentioning
confidence: 87%
“…1983a ; Pupo & Richardson, 1995 ;Gordon, 1997). These investigations have provided strong support for the idea that E. coli is essentially clonal (Selander et al, 1987).…”
Section: Introductionmentioning
confidence: 56%
“…In excess of 500 mice were collected on 6 occasions during the summer and autumn of 1993/94 by establishing trapping transects in a single field on each property. Further details of the age and sex structure of the mouse population are presented by Gordon (1997).…”
Section: Methodsmentioning
confidence: 99%
“…The Lac+ Cit-isolates were presumed to be E. coli and the identifications were subsequently confirmed using additional biochemical criteria. Further details of the clone isolation and identification procedures are given by Gordon (1997).…”
Section: Isolation and Characterization Of Bacteriamentioning
confidence: 99%